Comparison and evaluation of measured and simulated high-frequency capacitance-voltage curves of MOS structures for different interface passivation parameters - Sevillano Bendezú, Miguel Ángel (2019)
I would like to thank the National Council of Science, Technology and Technological Innovation (Concytec) from Peru for the award of a scholarship which made it possible to do this research work.